2005
DOI: 10.1074/jbc.m413343200
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling of Hepatic Endoplasmic Reticulum-associated Proteins in an Animal Model of Insulin Resistance and Metabolic Dyslipidemia

Abstract: Hepatic insulin resistance and lipoprotein overproduction are common features of the metabolic syndrome and insulin-resistant states. A fructose-fed, insulin-resistant hamster model was recently developed to investigate mechanisms linking the development of hepatic insulin resistance and overproduction of atherogenic lipoproteins. Here we report a systematic analysis of protein expression profiles in the endoplasmic reticulum (ER) fractions isolated from livers of fructose-fed hamsters with the intention of id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 65 publications
4
36
1
Order By: Relevance
“…The expression of ERp29 reaches its highest levels in secretory cells; seems to play an important role in protein folding; consists of two domains of which the N-terminal domain of ERp29 resembles the thioredoxin module of PDI [26]; and has been shown to associate with GRP78 and GRP94 [27]. Recently, Morand et al [11] profiled hepatic ER-associated proteins from control and fructose-fed (insulin-resistant) hamsters using 2-DE and MS and found ERp29 to be 4.5-fold down-regulated in fructose-fed hamster livers. In our study, we found ERp29 to be significantly decreased in MIN-6(H) cells compared to MIN-6(L) cells that maintain their GSIS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of ERp29 reaches its highest levels in secretory cells; seems to play an important role in protein folding; consists of two domains of which the N-terminal domain of ERp29 resembles the thioredoxin module of PDI [26]; and has been shown to associate with GRP78 and GRP94 [27]. Recently, Morand et al [11] profiled hepatic ER-associated proteins from control and fructose-fed (insulin-resistant) hamsters using 2-DE and MS and found ERp29 to be 4.5-fold down-regulated in fructose-fed hamster livers. In our study, we found ERp29 to be significantly decreased in MIN-6(H) cells compared to MIN-6(L) cells that maintain their GSIS.…”
Section: Discussionmentioning
confidence: 99%
“…Many chaperones are heat shock proteins, that is, proteins expressed in response to elevated temperatures or other cellular stresses, and include 78-kDa glucose-regulated protein (GRP78), GRP58, GRP94, protein disulphide isomerase (PDI), calreticulin, 29-kDa ER protein (ERp29). Altered expression levels of several proteins including GRP78, GRP94 and PDI have been shown to be associated with the pathophysiology of diabetes [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…P-gp protein also functions as an ER chaperone protein to participate in the ER stress response by directly or indirectly transporting unfolded or misfolded protein and it could also provide protection for cells through inhibition of caspase-dependent cell apoptosis (17,18). In the present study, the expression levels of the P-gp protein were studied in the HepG2 cells at 6, 12, 24, 48 and 72 h post high-dose insulin exposure.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that IR-induced hyperinsulinemia promotes the expression of P-gp, resulting in anticancer drug resistance in tumor cells (16). In addition, P-gp also plays protective roles as a chaperone for the transport of unfolded proteins during the ER stress reaction (17,18). During the process of IR induction in the HepG2 cells, the expression of MDR protein P-gp was significantly upregulated.…”
Section: Upregulation Of P-gp In the Hepg2 Cells During The Inductionmentioning
confidence: 99%
“…The expression of mdr1 in cells can be modified by several factors including stress signals and the metabolic and nutritional state [22][23]. P-gp can also play a role in the UPR, either directly by transporting misfolded proteins or indirectly by interacting with chaperones, conferring resistance to UPR-stimulated caspase-dependent apoptosis [23][24]. This suggests that MDR in tumors maybe related to the glucose abnormalities, ER stress, and the upregulation of mdr1.…”
mentioning
confidence: 99%